PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN KETERAMPILAN MENULIS CERITA ANAK KELAS V SEKOLAH DASAR NEGERI 21 PEKANBARU - Kurniaman, Otang Kurniaman Otang; Marhadi, Hendri Marhadi Hendri; ', Mardiah Mardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study aims to improve the skills of writing children's stories Elementary School fifth grade students through the application of the model 21 Pekanbaru Contextual Teaching And Learning (CTL). The subjects were students of class V SD Negeri 21 Pekanbaru the academic year 2013/2014 the number of students as many as 40 people. While the object of this research is to improve children's story writing skills through the application of the Contextual Teaching and Learning (CTL). The application is done in two cycles. The first cycle consists of two meetings with one daily tests at the end of the cycle and the second cycle consists of two meetings with one daily tests at the end of the cycle. Data collection instruments in this assessment is the observation sheet teacher and student activities and student skill assessment sheet results. Before taking action with an average of 61.62. While the value of the minimum completeness criteria 65. Among the students numbered 40 people only 18 people who reach KKM with the classical percentage of 45%. In the first cycle of daily tests the skills of students with an average of 66.80, while the daily test cycle II increased by an average of 80.68. Instrument data collection using observation sheets teacher activity and student activity observation sheet during the learning process takes place in class V SD Negeri 21 Pekanbaru. The percentage of activity of teachers in the first cycle the first meeting with the average 65%, at a meeting II increased by an average of 75%. In the second cycle the first meeting of an average percentage of 82.5%, at the second meeting of an average percentage of 95%. Furthermore, the percentage of student activity first cycle of the first meeting of an average percentage of 55.62%, in the second meeting peesentase average of 70.89%. In the second cycle the first meeting persentasse average of 84.28%, in the second meeting of an average percentage of 94.03%. From the above shows that through the application of models Contextual Teaching and Learning (CTL) to improve the writing skills of children's stories in learning Indonesian Elementary School fifth grade 21 Pekanbaru, unacceptable.Keywords : Model Contextual Teaching And Learning (CTL), Writing Skills